Viral antibody dynamics in a chiropteran host. (13th November 2013) - Baker, Kate S.; Suu‐Ire, Richard; Barr, Jennifer; Hayman, David T. S.; Broder, Christopher C.; Horton, Daniel L.; Durrant, Christopher; Murcia, Pablo R.; Cunningham, Andrew A.; Wood, James L. N.; Boots, Mike
Summary Bats host many viruses that are significant for human and domestic animal health, but the dynamics of these infections in their natural reservoir hosts remain poorly elucidated. In these, and other, systems, there is evidence that seasonal life‐cycle events drive infection dynamics, directly impacting the risk of exposure to spillover hosts. Understanding these dynamics improves our ability to predict zoonotic spillover from the reservoir hosts. To this end, we followed henipavirus antibody levels of >100 individual E. helvum in a closed, captive, breeding population over a 30‐month period, using a powerful novel antibody quantitation method. We demonstrate the presence of maternal antibodies in this system and accurately determine their longevity. We also present evidence of population‐level persistence of viral infection and demonstrate periods of increased horizontal virus transmission associated with the pregnancy/lactation period. The novel findings of infection persistence and the effect of pregnancy on viral transmission, as well as an accurate quantitation of chiropteran maternal antiviral antibody half‐life, provide fundamental baseline data for the continued study of viral infections in these important reservoir hosts.